The JCMT Plane Survey: early results from the ℓ = 30° field. Issue 4 (16th September 2015) - Moore, T. J. T.; Plume, R.; Thompson, M. A.; Parsons, H.; Urquhart, J. S.; Eden, D. J.; Dempsey, J. T.; Morgan, L. K.; Thomas, H. S.; Buckle, J.; Brunt, C. M.; Butner, H.; et al.
Abstract: We present early results from the JCMT (James Clerk Maxwell Telescope) Plane Survey (JPS), which has surveyed the northern inner Galactic plane between longitudes ℓ = 7° and ℓ = 63° in the 850-μm continuum with SCUBA-2 (Submm Common-User Bolometer Array 2), as part of the JCMT Legacy Survey programme. Data from the ℓ = 30° survey region, which contains the massive-star-forming regions W43 and G29.96, are analysed after approximately 40 per cent of the observations had been completed. The pixel-to-pixel noise is found to be 19 mJy beam −1 after a smooth over the beam area, and the projected equivalent noise levels in the final survey are expected to be around 10 mJy beam −1 . An initial extraction of compact sources was performed using the FellWalker method, resulting in the detection of 1029 sources above a 5σ surface-brightness threshold. The completeness limits in these data are estimated to be around 0.2 Jy beam −1 (peak flux density) and 0.8 Jy (integrated flux density) and are therefore probably already dominated by source confusion in this relatively crowded section of the survey. The flux densities of extracted compact sources are consistent with those of matching detections in the shallower APEX (Atacama Pathfinder Experiment) Telescope Large Area Survey of the Galaxy (ATLASGAL) survey. We analyse the virial and evolutionary state of the detected clumps in the W43 star-forming complex and find that they appear younger than the Galactic-plane average.